Progress on drinking water research - Lefebvre, Mathis H.; Roux, Matheo M. (Nova Science Publishers, Inc., 2008)
"This book focuses on worldwide research on contamination, toxicity and treatment of drinking water. Water of sufficient quality to serve as drinking water is termed potable water whether it is used as such or not. Although many sources are utilized by humans, some contain disease vectors or pathogens and cause long-term health problems if they do not meet certain water quality guidelines. Water that is not harmful for human beings is sometimes called safe water, water which is not contaminated to the extent of being unhealthy. The available supply of drinking water is an important criterion of carrying capacity, the population level that can be supported by planet Earth."--BOOK JACKET.